2020
DOI: 10.1136/bmjopen-2020-038214
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perceived health benefits of individuals with a disability participating in sport: A systematic review protocol

Abstract: IntroductionSports participation has many physical and mental health benefits for individuals with a disability, including improved functionality and reduced anxiety. Despite this, a large proportion of individuals with a disability are inactive. This review will be the first to synthesise the literature on the experiences and perceived health benefits of sport participation for children, adolescents, adults, elite athletes and veterans with a disability. Investigation of these phenomena will enable an underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Despite its subjective nature, wellbeing is a valid outcome that informed us of how parents thought their child was feeling, by holistically integrating both mental and physical health dimensions. Children and adolescents with disabilities who were able to self-report on their experience, previously highlighted the importance of the happiness and enjoyment provided by taking part in sports [ 21 ]. Likewise, in typically developing children and youth, psychological and social constructs that showed positive associations with sports participation included wellbeing, enjoyment, as well as mental health and perceived health [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its subjective nature, wellbeing is a valid outcome that informed us of how parents thought their child was feeling, by holistically integrating both mental and physical health dimensions. Children and adolescents with disabilities who were able to self-report on their experience, previously highlighted the importance of the happiness and enjoyment provided by taking part in sports [ 21 ]. Likewise, in typically developing children and youth, psychological and social constructs that showed positive associations with sports participation included wellbeing, enjoyment, as well as mental health and perceived health [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In typically developing children, several studies demonstrated the protective effect of increased physical activity against depressive and anxiety symptoms throughout school age and adolescence [ 23 , 24 , 25 ]. In adults with severe neurological impairments the practice of Boccia demonstrated positive influences on psychological health and mood [ 13 ] while young people with disabilities who practised sports reported improvements in confidence and self-esteem [ 21 ]. Children with PIMD have numerous reasons to experience discomfort and pain, and in our study adaptive sports seemed to be able to provide relief and improved comfort (reflecting the physical component of wellbeing) for a majority of children.…”
Section: Discussionmentioning
confidence: 99%
“…Napjainkban a fizikai inaktivitás növekedése világméretű probléma, így számos tanulmány foglalkozik akár az inaktivitás okaival, vagy annak nemzetgazdasági kérdéseivel akár a sportolás egészségben betöltött szerepével [1]; [2]; [3], mentális egészségre gyakorolt hatásaival [4], vagy a sportolás hiányának egészségre gyakorolt hatásaival [5], mely már a fogyatékossággal élő személyek célcsoportrjában is vizsgálatra került [6]; [7].…”
Section: Bevezetésunclassified
“…Training for particular sports is associated with the permanent evaluation of one's choices, including healthpromoting behaviors. Practicing sport has a great educational potential in the field of shaping social attitudes; it is a form of rehabilitation, and it also creates opportunities for social integration [23]. The physical activation of people with disabilities requires support from their family and friends in solving everyday problems [14,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%